2008
DOI: 10.1128/jb.01092-07
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Profiling of the Stringent Response in Escherichia coli

Abstract: The bacterial stringent response serves as a paradigm for understanding global regulatory processes. It can be triggered by nutrient downshifts or starvation and is characterized by a rapid RelA-dependent increase in the alarmone (p)ppGpp. One hallmark of the response is the switch from maximum-growth-promoting to biosynthesis-related gene expression. However, the global transcription patterns accompanying the stringent response in Escherichia coli have not been analyzed comprehensively. Here, we present a tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
361
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(384 citation statements)
references
References 107 publications
21
361
1
1
Order By: Relevance
“…(Fig. 3C and Table S3) were fully consistent with the known effects of ppGpp, which changes gene expression in patterns different from those we observe for the adaptive mutations (30,31) and which is generally observed to increase pausing and decrease elongation rate (12,13) (opposite to that observed for the adaptive mutant RNAPs). Therefore we have ruled out the possibility that the mutations are adaptive simply because they mimic the effects of ppGpp.…”
Section: Discussionsupporting
confidence: 61%
“…(Fig. 3C and Table S3) were fully consistent with the known effects of ppGpp, which changes gene expression in patterns different from those we observe for the adaptive mutations (30,31) and which is generally observed to increase pausing and decrease elongation rate (12,13) (opposite to that observed for the adaptive mutant RNAPs). Therefore we have ruled out the possibility that the mutations are adaptive simply because they mimic the effects of ppGpp.…”
Section: Discussionsupporting
confidence: 61%
“…Recent genome-wide expression studies have reported that at least five and as many as 40 r-protein transcripts decrease following amino acid limitation (22,23). However, as in the earlier studies, conclusions about the mechanistic basis for the decrease in r-protein mRNA levels were constrained by reports that r-protein transcripts had lifetimes of only a few seconds when they were translationally repressed (24,25).…”
mentioning
confidence: 45%
“…However, amino acid starvation triggers a major re-orchestration of the genome-wide transcription pattern 9,17,18 which results in a change in the cellular concentration of most RNA species shortly after the onset of starvation (refs. 18-20 and our manuscript in preparation). Therefore, there is no endogenous reference transcript which is known to be suitable for comparing the cellular levels of tRNA (or any other RNA species) during amino acid starvation to the levels during steady-state growth.…”
Section: The Important Choice Of a Standard For Normalizationmentioning
confidence: 86%